Performance evaluation of linear crosstalk impairments in array waveguide grating router in WDM networks - M. Karfaa, Yasin; Ismail, M.; F. M., Abbou; Shaari, S. (Faculty of Electrical Engineering, 2007)

(untitled)
Theoretical analysis is carried out to evaluate the performance of a Wavelength Division Multiplexing (WDM) network transmission system in the presence of crosstalk due to an array waveguide grating router. It is found that linear crosstalk induced by the array waveguide induces higher penalty when the number of add/drop channels is increased and therefore imposes severe limitation on the maximum number of add/drop channels and the number of users accessing the WDM network.